2005
DOI: 10.1071/mf04195
|View full text |Cite
|
Sign up to set email alerts
|

Investigations into the taxonomy, toxicity and ecology of benthic cyanobacterial accumulations in Myall Lake, Australia

Abstract: Large benthic accumulations of cyanobacteria occur in sheltered embayments within Myall Lake, New South Wales, Australia. The lake is shallow, with the entire bottom within the euphotic zone, and it is generally considered pristine, having low nutrient concentrations. The accumulations are highly organic and contain a mix of species mainly from the order Chroococcales, with two forms of Aphanothece being dominant. However polymerase chain reaction (PCR) analysis indicates a close similarity to Microcystis flos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 28 publications
0
23
1
Order By: Relevance
“…High river flows have the ability to pick up rocks and pebbles, and thereby remove attached mat material from substrates (Biggs & Close 1989). Water turbulence has been previously described as a major controlling factor for benthic Cyanobacteria in river systems (Biggs 1990, Milne & Watts 2006, Wood et al 2007, lake systems (Johnson & Castenholz 2000, Dasey et al 2005, and marine environments (Thacker & Paul 2001). The ability of river flow to flush Phormidium mats has led local government agencies in the Wellington region to adopt this measure as one of the factors used to predict Phormidium mat percentage coverage (Milne & Watts 2006).…”
Section: Phormidium Mat Presence and Physicochemical Parametersmentioning
confidence: 99%
“…High river flows have the ability to pick up rocks and pebbles, and thereby remove attached mat material from substrates (Biggs & Close 1989). Water turbulence has been previously described as a major controlling factor for benthic Cyanobacteria in river systems (Biggs 1990, Milne & Watts 2006, Wood et al 2007, lake systems (Johnson & Castenholz 2000, Dasey et al 2005, and marine environments (Thacker & Paul 2001). The ability of river flow to flush Phormidium mats has led local government agencies in the Wellington region to adopt this measure as one of the factors used to predict Phormidium mat percentage coverage (Milne & Watts 2006).…”
Section: Phormidium Mat Presence and Physicochemical Parametersmentioning
confidence: 99%
“…Charophytes might contribute a substantial amount of organic material to gyttja where water is shallow. Dasey et al (2005) report gyttja with 14.9 g DW/l. Typically the gyttja layer is 0.25-0.5 m thick, which amounts to 3,725-7,450 g DW/m 2 .…”
Section: Patchinessmentioning
confidence: 95%
“…The natural and conservational value of the Myall Lakes system is internationally recognised, with the area being listed as a Ramsar Wetland of International Importance (NPWS, 2002). In 1999, studies of the limnology and ecology of the Myall Lakes revealed extensive areas (800 ha) of uncompacted, cyanobacterial 'ooze', or gyttja, in the northern-most lake, Myall Lake (Dasey et al, 2004). Taxonomic examination of the gyttja indicated it was largely composed of cyanobacteria (Aphanothece) from the order Chroococcales.…”
Section: Introductionmentioning
confidence: 98%
“…Cyanobacterial accumulations, or mats, have the potential to spread over large areas within affected waterways (Bowling & Baker, 1996) and receive considerable attention from authorities in the form of water quality monitoring, clean-up programmes and public safety assessments (Dasey et al, 2004).…”
Section: Introductionmentioning
confidence: 99%